2006
DOI: 10.1002/pssb.200541364
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy of open‐ended Single Wall Carbon Nanotubes under pressure: effect of the pressure transmitting medium

Abstract: We performed high pressure Raman experiments on purified open-ended single wall carbon nanotubes using different pressure transmitting media (paraffin oil, argon and 4 : 1 methanol ethanol mixture) and two excitating wavelength (514.5 nm and 632.8 nm). We state that the behavior of the Raman spectrum under pressure is significantly dependent on the pressure transmitting medium. This result points out the relevance of the interactions between the medium and the nanotubes, at the origin of the disagreement betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 43 publications
8
39
0
Order By: Relevance
“…The plateau commencing at about 1.5 GPa with liquid argon is qualitatively similar to the work of Merlen et al [8] who observed a plateau commencing at 10 GPa with open-ended SWNTs. The openended SWNTs used in their experiment would offer more absorption sites for liquid argon than in our experiment thus allowing the G-band to continue shifting to higher pressures, so the hypothesis of shifts in the Raman peak being in part caused by absorption of solvents onto the surface of the nanotubes is supported.…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…The plateau commencing at about 1.5 GPa with liquid argon is qualitatively similar to the work of Merlen et al [8] who observed a plateau commencing at 10 GPa with open-ended SWNTs. The openended SWNTs used in their experiment would offer more absorption sites for liquid argon than in our experiment thus allowing the G-band to continue shifting to higher pressures, so the hypothesis of shifts in the Raman peak being in part caused by absorption of solvents onto the surface of the nanotubes is supported.…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…We use argon, oxygen, and methanol-ethanol in the proportion 4:1. Recent studies of Merlen et al 8,9 on CNT bundles ͑CNTs grown by the arc discharge method͒ show no frequency dependence on the media. In this study we use CNTs grown using the catalytic chemical vapor deposition method ͑CCVD͒, which leads to the formation of individual CNT and small bundles allowing nanoscale pressure effects to be investigated.…”
mentioning
confidence: 97%
“…Previous investigations by Merlen et al [12,13] using the same wavelengths and same diameter range but with open-ended tubes and different pressure transmitting media, has also recorded such a disappearance of the BWF peak, but this disappearance was only recorded after 10 GPa. Moreover using argon in one of their investigations, this disappearance is observed around 20 GPa.…”
Section: Discussionmentioning
confidence: 69%